Does students’ self-determined motivation toward Physical Education influence the effectiveness of a fitness teaching unit? A cluster-randomized controlled trial and cluster analysis. - Guijarro-Romero, Santiago; Mayorga-Vega, Daniel; Casado-Robles, Carolina; Viciana-Ramírez, Jesus (Elsevier, 2020)
Objective: The aim was to compare the effect of a Physical Education (PE)-based fitness teaching unit to improve cardiorespiratory fitness levels between students’ motivational profiles toward PE in high-school students using cluster analysis. Method: One hundred and eighty-one high school students (final sample 165, 52.1% females; Mage = 12.9 ± 0.9) from nine pre-established classes were cluster-randomly assigned into an experimental group (n = 120) and control group (n = 61). The experimental group performed a fitness teaching unit twice a week for nine weeks. Students’ baseline of self-determined motivation toward PE was measured by the Spanish version of the Perceived Locus of Causality-II Scale. Cardiorespiratory fitness was measured before and after the intervention through the 20-meter shuttle run test. Results: Based on a two-stage cluster analysis approach, four clusters were identified in both groups. Results showed that the experimental group students within the high self-determined motivational profiles toward PE (i.e., clusters 2 and 4) statistically significantly improved their cardiorespiratory fitness levels compared with the control group students in cluster 2 (i.e., those with moderate self-determined motivational profile toward PE) (p < 0.05; d = 0.37-0.48). However, statistically significant differences between the students with a moderate autonomous motivation profile toward PE (i.e., cluster 3 of the experimental group) and the control group students in clusters 2 and 3 were not found (p > 0.05). Conclusions: With the objective of increasing all students’ cardiorespiratory fitness levels, PE teachers should encourage students’ motivation toward PE applying specific motivational strategies during PE lessons.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/16062
Keywords: Educación física para adolescentes; Adolescentes - Salud; Autonomous motivation; Cardiovascular endurance; Educative intervention; Person-centered approach; High school students